Lateralized suckling in domestic horses (Equus caballus) - Komárková, Martina; Bartošová, Jitka (Animal cognition, 2013)
Brain lateralization enables preferential processing of certain stimuli and more effective utilization of these stimuli in either the left or the right cerebral hemisphere. Horses show both motor and sensory lateralization patterns. Our aim was to determine whether a lateralized response could be detected in foals during the naturally side-biased behaviour, suckling. The foals' preferred suckling side could be the effect of either visual or motor lateralization. In the case of a visual lateralized response, foals are expected to suck more often from the mother's right side, so potential danger can be detected by the better adapted right hemisphere (i.e. left eye). Motor lateralization can be identified when a foal will suck predominantly from one side, either left or right. We found no population trend in the preferred suckling side, but we detected significant differences amongst individual foals. One-third (35.4 %) of 79 foals showed a strong, either right or left side preference which increased with age. The mothers did not influence the foals' suckling side preferences either by side-biased rejection or termination of suckling. According to our findings, a general pattern of sucking with the left eye open for better danger detection and recognition is unlikely in foals up to 7 months old. Foals of this age are probably young or fully focused on suckling and rely on their mothers' vigilance. Individual side preferences amongst foals are suggested to be based on motor lateralization.
Keywords: Animals; Horses; Time Factors; časové faktory; věkové faktory; funkční lateralita; Female; Animals, Suckling; zvířata; mužské pohlaví; kojená zvířata; Male; Age Factors; Functional Laterality; ženské pohlaví; koně